Serum biochemical markers of central nerve system damage in children with acute elemental mercury intoxicatıon. (January 2014) - Yılmaz, F. M.; Yılmaz, H.; Tutkun, E.; Uysal, S.; Carman, K. B.; Dİlber, C.; Ercan, M.
<x xml:space="preserve">Abstract</x> Objective. Acute mercury intoxication among children can occur through unintentional exposure, and neurotoxicity is one of the main findings in acute exposures. In this study, we aimed to study the central nerve system markers, namely neuron-specific enolase (NSE), S100B, and glutamate receptor (GRIA 1) levels and discuss the mechanisms of central nerve system damage and whether these parameters could be used as markers of acute elemental mercury intoxication neurotoxicity. Materials and methods. This is a case-control study which includes 169 children with acute elemental mercury intoxication, who were exposed to mercury in the school laboratory from a broken jar, and 45 sex- and age-matched controls without mercury exposure. Patient group were divided into three subgroups according to the neurological examination performed during the admission. Neuropathy Group included the children with neurological symptoms including peripheral neuropathy and decreased muscle strength (n = 39) (with or without dilated pupils). Dilated Pupil Group included the children who had mid-dilated/dilated pupils (n = 52). Asymptomatic Exposure Group included the children who did not have any neurological symptoms (n = 78). Serum NSE, S100B, GRIA 1, blood, and urine mercury levels were determined. Results. NSE, S100B, GRIA 1, and blood mercury levels were significantly higher in exposed group than the nonexposed subjects (Median values NSE 22.4 ng/mL, 17.2 ng/mL; S100B 0.09 ng/mL, 0.08 ng/mL; GRIA 1 70.6 pg/mL, 54.1 pg/mL, and blood mercury 15.2 μg/L, 0.23 μg/L for exposed and nonexposed groups, respectively). GRIA 1 levels found to differ between exposed and nonexposed groups and it has also been found to be increased in the subgroups with positive neurological findings compared to that in neurological finding negative groups. S100B levels were found to be increased in exposed and having neurological symptom groups. There was not a significant difference between exposed-not having neurological symptom patients and control group. NSE levels were found to be higher in all subgroups when compared to those in controls, however there was not a significant difference between the subgroups. Conclusion. Serum NSE, GRIA 1, and S100B were increased with mercury exposure. GRIA 1 and S100B levels were observed to have the power to discriminate neurological symptom positive and negative groups. The increase in S100B levels are thought to be protecting the neurons and preventing further NSE elevations.